AKT1 and genetic vulnerability to bipolar disorder. (February 2020) - Millischer, Vincent; Matheson, Granville J.; Martinsson, Lina; Römer Ek, Inger; Schalling, Martin; Lavebratt, Catharina; Backlund, Lena
Highlights: AKT1 encodes a serine/threonine kinase and is implicated in lithium signaling. Genetic variations of AKT1 have been associated with bipolar disorder (BD). Here, we were not able to replicate previously reported associations. Genome wide association data did not reveal any signal for BD in the AKT1 region. Abstract: AKT1 encodes a serine/threonine kinase that has as one of its best-known substrates glycogen synthase kinase-3 (GSK3), a primary target for lithium. AKT1 has been previously been implicated as a vulnerability gene for bipolar disorder (BD). We aimed to associate genetic variants in the AKT1 gene with subgroups of BD. BD patients from a Swedish cohort ( N = 831) were phenotyped in regards to their psychotic episodes according to mood-congruence in depression and manias, and compared to controls ( N = 1, 496). All participants were genotyped for SNPs in AKT1 previously implicated to have a role: rs3730358, rs1130214 and rs3803300. None of the effects reported in earlier studies were statistically significant, including the association between rs3803300 and BD without any psychotic symptoms, rs3803300 and mood-congruent psychosis, rs3803300 and the combined groups, as well as the association between the haplotypes formed by rs3730358 and rs1130214 and risk for BD. In a Bayesian analysis, all Bayes' Factors using default priors supported the null hypothesis in the replication set by a factor of between 5 and 1300 times. Analysis of genome wide association data did not reveal any association between BD and the AKT1 region. We conclude AKT1 is less likely to be a vulnerability gene in BD.